(untitled) (Web of Teachers: Inderscience Research, 2026)
English has become the dominant language of global scientific communication, particularly in the fields of medicine and healthcare. As a result, medical students worldwide must develop proficiency not only in general English but also in specialized medical terminology and professional communication. English for Specific Purposes (ESP) has emerged as an effective pedagogical approach that focuses on the language needs of learners in specific professional and academic contexts. In medical education, ESP plays a crucial role in preparing students to communicate effectively in clinical environments, understand medical literature, and participate in international medical discourse. This article examines the role of ESP in teaching Medical English and discusses its importance in modern medical education. The paper also explores the principles of ESP instruction, teaching strategies, and the benefits of integrating ESP-based courses into medical curricula. Furthermore, it highlights the need for collaboration between language educators and medical specialists in designing effective ESP programs. The study concludes that ESP-based Medical English instruction significantly enhances students’ professional communication skills and prepares them for participation in the global medical community.